Global Trade Recalibration In The Post-Pandemic Era: Analyzing Structural Shifts, Market Volatility, And Policy Responses Across Developing Economies - Afdal; Arista (CV. SINAR HOWUHOWU, 2025)
The post-pandemic global economy has entered a period of profound realignment, marked by shifting trade patterns, heightened market volatility, and uneven recovery trajectories across developing regions. This study investigates the structural transformations reshaping global trade flows after COVID-19, focusing on supply chain reconfiguration, digital trade expansion, and the resurgence of regional economic blocs. Using a mixed comparative framework that integrates trade-intensity metrics, volatility indices, and policy mapping from 28 developing economies, the analysis reveals three major findings. First, global trade recalibration is characterized by a transition from hyper-globalization toward strategic regionalism, driven by risk mitigation, geopolitical tensions, and the pursuit of supply chain resilience. Second, commodity-dependent economies experience sharper volatility due to price instability and weakened demand from advanced economies. Third, government policy responses—ranging from export diversification and industrial upgrading to digital trade facilitation—play a decisive role in shaping post-pandemic recovery trajectories. The study concludes that the future of global trade in developing economies will depend on adaptive policies, technological modernization, and cross-border cooperation to navigate the uncertainties of an evolving global economic landscape.